STRATEGI GAYA KOMUNIKASI DALAM PROSES VOICE OVER BERITA KABAR SRIWIJAYA - Tria Febriyati; Rahma Santhi Zinaida (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This internship report discusses communication style strategies in the voice-over process for the news program Kabar Sriwijaya at Sriwijaya TV. The internship was conducted to understand the application of effective communication techniques in delivering information to audiences through television media. The main focus of this study is the use of communication styles by voice-over talents in presenting news scripts so that messages can be conveyed clearly, attractively, and easily understood by viewers.The methods used in preparing this report include participatory observation, direct practice, documentation, and active involvement in the news production process throughout the internship period. The author participated in various stages of work, including studying news scripts, recording voice-overs, adjusting intonation and speech tempo, and taking part in evaluations of recording results with the production team. In addition, the author gained experience in archiving reporting materials used for news editing purposes.The results of the internship indicate that the effectiveness of news delivery through voice-over is greatly influenced by the communicator’s ability to apply clear articulation, appropriate intonation, controlled speech tempo, and emphasis on important information. The selection of a suitable tone of voice according to the nature of the news also plays a significant role in building credibility and enhancing the attractiveness of the broadcast. Furthermore, coordination among voice-over talents, reporters, editors, and the production team is an important factor in producing high-quality news programs.Through this internship, the author gained a deeper understanding of the role of communication in television broadcasting and improved professional skills in journalism and mass media.